Synthesis, Cyclic Voltammetric, Electrochemical, and Gravimetric Corrosion Inhibition Investigations of Schiff Base Derived from 5,5-Dimethyl-1,3-cyclohexanedione and 2-Aminophenol on Mild Steel in 1 M HCl and 0.5 M H2SO4 - Ragi Kooliyat; Joby Thomas Kakkassery; Vinod P. Raphael; Sini Varghese Cheruvathur; Binsi M. Paulson (International Journal of Electrochemistry)
Schiff base 2,2’-(5,5-dimethylcyclohexane-1,3-diylidene)bis(azan-1-yl-1-ylidene) diphenol (DmChDp) was synthesized and characterized using spectroscopic methods (IR, UV, NMR, and Mass) and cyclic voltammetric (CV) studies. The corrosion inhibition potency of (DmChDp) on mild steel (MS) in 1M HCl and 0.5M H2SO4 was investigated. The corrosion monitoring techniques employed for this purpose are gravimetric and electrochemical methods (EIS and potentiodynamic polarization studies). The study reveals that the Schiff base, DmChDp, acts as excellent corrosion inhibitor on mild steel in 1M HCl. DmChDp obeys Langmuir adsorption isotherm both in 1M HCl and 0.5M H2SO4 on MS. Polarization studies show that DmChDp behaves as a mixed type inhibitor in both media. Scanning electron microscopic analysis established the protective nature of DmChDp on mild steel surface. The impact of temperature on the corrosion of MS was also evaluated using gravimetric method.